REVERTER, S. (2022). Feminismo sin testamento. Castelló de la Plana: Publicacions de la Universitat Jaume I, Col. Sendes, 27 - Lara Muñoz, Rocío (Daimon Revista Internacional de Filosofia, 2025)
Reseña de REVERTER, S. (2022). Feminismo sin testamento. Castelló de la Plana: Publicacions de la Universitat Jaume I, Col. Sendes, 27.